Analysis of The Effectiveness of Visum Et Repertum Examination on Unidentified Corpses in the Criminal Investigation Process: Research Study at Bhayangkara Batam Hospital, Riau Islands Police - Syaiful Azwir; Soerya Respationo; Erniyanti Erniyanti (International Journal of Law, Crime and Justice, 2024)
The background of this research is the importance of the Visum et Repertum (VeR) examination in identifying victims and determining the cause of death, especially in cases of unidentified corpses that are often found in the Riau Islands area. Proper and accurate VeR checks are vital to support the criminal investigation process, provide justice for victims and their families, and maintain the integrity of the criminal justice system. The purpose of this study is to analyze the effectiveness of the VeR examination conducted at Bhayangkara Batam Hospital in assisting victim identification and supporting criminal investigations. The study also aims to identify the obstacles faced in the examination process and provide suggestions to improve its effectiveness. The purpose of this study is to analyze the effectiveness of the VeR examination conducted at Bhayangkara Batam Hospital in assisting victim identification and supporting criminal investigations. The study also aims to identify the obstacles faced in the examination process and provide suggestions to improve its effectiveness. The research method used is normative juridical with an empirical juridical approach at Bhayangkara Batam Hospital. The data was collected through in-depth interviews with forensic doctors, police investigators, and analysis of VeR documents and reports. The data obtained were analyzed using positive law theory from John Austin, legal system theory from Lawrence M. Friedman, and evidentiary law theory. The results showed that although the VeR examination at Bhayangkara Batam Hospital was generally effective, although there were several obstacles that affected the quality and speed of the examination, such as limited resources, medical personnel skills, and the condition of the corpses that were often decomposed. Suggested efforts to overcome these obstacles include improving forensic medical facilities and equipment, ongoing training for medical personnel, implementing standard protocols, and increasing cooperation between related agencies. Suggestions include the need for governments to invest more in forensic infrastructure, the importance of public education on missing persons reporting, and the need for increased collaboration and integrated training for investigators and forensic experts. With the implementation of these suggestions, it is hoped that the effectiveness of VeR examinations can be improved, thereby supporting criminal investigations in a more efficient and fair manner.